Information System for Managing Work Requests and Monitoring Dental Prosthesis Laboratory Services at Quality Dental Care Semarang - Lie Eraldo Manason; Dody Indra Sumantiawan (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The denture laboratory plays a crucial role in supporting dental clinic services, especially in providing prosthetic products that are delivered on time and meet the medical needs of patients. At Quality Dental Care Semarang, the management of job requests and the recording of service process statuses are still done manually, which can lead to delays in information flow, difficulties in monitoring job statuses, and obstacles in performance evaluation. This study aims to develop a web based information system for managing job requests and monitoring the services of the denture laboratory using PHP, HTML, and MySQL. Through the Research and Development (RAD) method, the stages involved include needs analysis, design, implementation, and functional testing. The developed system provides features for recording job requests, monitoring process statuses, recording completion times, and generating reports, all integrated into a single database. The results of functional testing show that this system successfully improves workflow organization, enhances information management efficiency, and facilitates job status monitoring.